Pengaruh Down Payment dan Insentif Pajak Kendaraan PPNBM Terhadap Penjualan Mobil selama Pandemi Covid-19 - Nurwati, Nurwati; Efriadi, Adi Rizfal; Supriadi, Sendi (Universitas 17 Agustus 1945 Jakarta, 2022)
The research conducted aims to examine government policies on the decline in sales of four-wheeled vehicles, government policies that have been implemented are fiscal taxes by providing four-wheeled PPnBM tax incentives for 1500 cc vehicle types with the number of passengers less than 10 people with a tax incentive rate of 100%. The type of research conducted is descriptive associative regarding the influence between variables. The data used is from GAIKINDO and OTO.COM and is secondary. The research method used is quantitative and the sample technique uses purposive sampling. The analytical technique used by the researcher is multiple linear regression analysis using SPSS version 26. The variables used in this study are Down Payment, Incentives, PPnBM as the independent variable and Sales as the dependent. The result of the research is that the down payment variable has a negative effect on car sales and the PPnBM incentive variable has a positive effect on car sales and the two variables simultaneously affect car sales